2018
DOI: 10.1523/eneuro.0103-18.2018
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol Drives the Anorexigenic Activity of Proopiomelanocortin Neurons in Female Mice

Abstract: Energy balance is regulated by anorexigenic proopiomelanocortin (POMC) and orexigenic neuropeptide Y/agouti-related peptide (NPY/AgRP) neurons of the hypothalamic arcuate nucleus. POMC neurons make extensive projections and are thought to release both amino acid and peptide neurotransmitters. However, whether they communicate directly with NPY/AgRP neurons is debated. Initially, using single-cell RT-PCR, we determined that mouse POMCeGFP neurons express Slc17a6 (Vglut2) and Slc18a2 (Vmat2), but not Slc31a1 (Vg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
49
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(58 citation statements)
references
References 89 publications
(130 reference statements)
6
49
2
1
Order By: Relevance
“…Using a newly developed CRISPR strategy, we have shown that this single vector approach reduced the expression of Kcnq3 in NPY/AgRP neurons, resulting in molecular, cellular, and behavioral changes. While this approach was previously validated [41], we have extended this finding using a stringent method of harvesting healthy cells paired with a quantitative measure of relative gene expression [53]. Furthermore, we have confirmed that this change was not due to the surgery, SaCas9-alone, or fluorophore.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Using a newly developed CRISPR strategy, we have shown that this single vector approach reduced the expression of Kcnq3 in NPY/AgRP neurons, resulting in molecular, cellular, and behavioral changes. While this approach was previously validated [41], we have extended this finding using a stringent method of harvesting healthy cells paired with a quantitative measure of relative gene expression [53]. Furthermore, we have confirmed that this change was not due to the surgery, SaCas9-alone, or fluorophore.…”
Section: Discussionsupporting
confidence: 57%
“…After three weeks, mice underwent OVX and were subsequently given EB-treatment on the two days prior to sacrifice. Brain slices were prepared, and cells harvested as previously described [53] and analyzed with qPCR. We found that the KCNQ3-KD group displayed a reduction in relative expression of Kcnq3 in NPY/AgRP neurons compared to the control group (Fig 2B), but Kcnq2 mRNA was not changed in NPY/AgRP neurons in response to Kcnq3 KD (Fig 2C).…”
Section: Crispr Kcnq3 Significantly Decreases Kcnq3 Expressionmentioning
confidence: 99%
“…neurons excites Kiss1 ARH neurons, an indication that POMC neurons may signal to Kiss1 ARH neurons the metabolic status of the organism. 76 Chronically, OVX Kiss1R KO females develop obesity, hyperleptinemia, reduced metabolism, and glucose intolerance in comparison to OVX females. 58 Therefore, the Kiss1R (GPR54) may play a role to link metabolic changes to reproduction in female rodents.…”
Section: Role Of Kiss1r (Gpr54) and Neuropeptide Ff Receptor 1 In Enementioning
confidence: 99%
“…Importantly, glutamate has been described to mediate the effect (excitation) that Kiss1 ARC neurons exert on POMC neurons, and to selectively inhibit AgRP neurons (10,64), which strongly supports a glutamatergic component in the phenotype of the Kiss1 ARC silenced mouse model (57). Moreover, the glutamatergic action of Kiss1 neurons onto neighboring POMC and AgRP neurons is gonadal hormone dependent, as it is enhanced by E2 in females (64,65), in line with the sex-dependent effect of kisspeptin on food intake in jerboa (50) and BW in Kiss1rKO mice (43), restricted to females (Fig. 1).…”
Section: Kiss1 Neurons Display Bidirectional Interactions With Agrp Amentioning
confidence: 82%